Exploring EFL Students’ Critical Thinking through Reflective Journal - Sunra, La (Celebes Journal of Language Studies, 2022)
Critical thinking, as one of the 21st century skills, is a necessary skill needed to prepare students for further studies and the workforce. This study aimed at exploring English students’ critical thinking skills through reflective journal. The study focused on two research questions: (1) To what extent does reflective journal enhance the EFL students’ critical thinking? (2) What aspect of EFL students’ critical thinking skills does enhance significantly? A quantitative and qualitative design were utilized. Applying purposive sampling technique, 30 EFL students who participated in micro teaching course in Universitas Negeri Makassar were taken as sample of the research. The instrument of this research was students’ reflective journals. The data collected were analyzed through descriptive statistical as well as qualitative analysis. The results of the research showed that the use of reflective journal in Micro Teaching course improves EFL students’ critical thinking skills in moderate way. The significant increase in students’ critical thinking takes place in evaluating aspect reaching approximately 70% increase. This indicates that reflective journal helps facilitate the EFL students improve their ability to develop their analysis in determining the strengths and weaknesses of their teaching practices in a factful and logical way. The study also indicated that some students still find it difficult to make final statement in conclusion as the best alternative solution to improve their practice in the future. Finally, the study implies that EFL teachers need to do their best to integrate critical thinking in their teaching either explicitly or implicitly.